2014
DOI: 10.1155/2014/793628
|View full text |Cite
|
Sign up to set email alerts
|

Serum Amyloid A as a Marker of Persistent Inflammation and an Indicator of Cardiovascular and Renal Involvement in Patients with Rheumatoid Arthritis

Abstract: Objectives. Rheumatoid arthritis (RA) is a systemic, inflammatory disease. Serum amyloid A (SAA) is an acute-phase protein, involved in pathogenesis of atherosclerosis. The aim of the study was to assess serum concentration of SAA in RA patients, with reference to other inflammatory parameters and markers of extra-articular involvement. Methods. The study population consisted of 140 RA patients, low/moderate disease activity (L/MDA) in 98 (70%) patients and high disease activity (HDA) in 42 (30%). Comprehensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 43 publications
2
59
0
3
Order By: Relevance
“…Individuals with benign tumors did not have significantly higher serum SAA levels than healthy persons [61], but SAA levels increased significantly as cancer progressed [56, 61, 90, 101, 104, 106]. The same effect was seen in patients with RA or osteoarthritis, whose serum SAA concentrations increased with the severity of the disease [83, 102, 107, 108]. Marhaug and Dowton [93] concluded that the serum SAA concentration is a very sensitive, but non-specific marker both in diagnosis, prognosis and monitoring of inflammatory and infectious diseases, just as in cancer [56, 61, 90, 105, 106].…”
Section: Production Of Human Saa Variantsmentioning
confidence: 99%
“…Individuals with benign tumors did not have significantly higher serum SAA levels than healthy persons [61], but SAA levels increased significantly as cancer progressed [56, 61, 90, 101, 104, 106]. The same effect was seen in patients with RA or osteoarthritis, whose serum SAA concentrations increased with the severity of the disease [83, 102, 107, 108]. Marhaug and Dowton [93] concluded that the serum SAA concentration is a very sensitive, but non-specific marker both in diagnosis, prognosis and monitoring of inflammatory and infectious diseases, just as in cancer [56, 61, 90, 105, 106].…”
Section: Production Of Human Saa Variantsmentioning
confidence: 99%
“…SAA may play an important, pathogenic role in the proinflammatory process of RA (Connolly et al, 2012). Moreover, studies have indicated increased serum levels of SAA in RA and found it to be strongly associated with disease activity (Targonska-Stepniak and Majdan, 2014). In the current study, increased levels of serum SAA were demonstrated in the CP group.…”
Section: Oral Diseasesmentioning
confidence: 99%
“…This circumstance holds true for RA, with elevated levels of both pro-inflammatory [e.g. C-reactive protein (CRP) (7)(8)(9)(10)(11), Tumor necrosis factor alpha (TNFα) (7,9,11), Interleukin-6 (IL-6) (7-12), IL-1β (7) and Serum Amyloid A (SAA) (10,13,14)] and prothrombotic markers [e.g. D-dimer (8,9,11,15,16), Fibrinogen (10,11,16,17), Tissue Factor (TF) (15), and von Willebrand factor (vWF) (8,16,18)], which is associated with one another (7,19) and with the risk of future cardiovascular complications (20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%